Impact of a Pediatric Cardiology Clinical Program on Congenital Heart Disease Outcomes in Guyana. (13th September 2017) - Isaac, Debra; Nagesh, Vikhashni; Bell, Alexandra; Soto, Rodrigo; Seepersaud, Marisa; Myers, Kimberley; Zahir, Saif
Background: Children with congenital heart disease (CHD) in Guyana have not historically been managed with timely intervention, increasing the likelihood of serious, irreversible complications. In 2014, a pediatric cardiology clinical program (Guyana Paediatric Cardiology Steering Committee [GPCSC]) and partnership with International Children's Heart Foundation (BabyHeart) was developed to improve CHD care.Objectives: To describe the characteristics of CHD in Guyanese children and to determine the impact of GPCSC on CHD outcomes.Methods: Qualitative comparison between CHD patients sent for surgery prior to GPCSC (pre-GPCSC cohort) and those managed through GPCSC (post-GPCSC cohort).Findings: Eighty-eight pre-GPHC patients were identified from 2005 to 2014. A total of 319 CHD patients were referred post-GPCSC. In all, 114 patients required surgical or catheterization procedures, with 74 patients prioritized for interventions within 29 months post-GPCSC. Mean age at surgery was 77 months in both cohorts, with younger children represented in the post-GPCSC cohort. Postoperative follow-up was more frequent post-GPCSC (100% vs 35%). Vital status of 48% of pre-GPCSC patients is unknown, with more pre-GPCSC patients known to be deceased compared with post-GPCSC (9% vs 5%). Pre-GPCSC patients had more incorrect diagnosis and inoperable disease when sent for surgery.Interpretation: Patients undergoing surgery post-GPCSC had more appropriate and timely interventions, better follow-up, and increased survival. The feasibility and positive impact of this collaborative pediatric cardiology clinical program in Guyana is demonstrated, with potential applicability for other low- and middle-income countries. Obstacles to referral of children with CHD in Guyana can begin to be addressed, with the goal of more complete access to timely intervention, and improved outcomes for these children.